Alternating voltage induced porous Co3O4 sheets: an exploration of its supercapacity properties. Issue 1 (2nd December 2014) - Jing, Mingjun; Yang, Yingchang; Zhu, Yirong; Hou, Hongshuai; Wu, Zhibin; Chen, Qiyuan; Ji, Xiaobo
Abstract : An alternating voltage induced method has been developed for the fabrication of porous Co3 O4 sheets. Abstract : An alternating voltage induced method has been developed for the fabrication of porous Co3 O4 sheets. The electrochemical investigation of Co3 O4 sheets in LiOH, NaOH and KOH electrolytes reveals that the size of the hydrated ionic radius can have impact on its ionic conductivity, resulting in the best rate behaviour in the KOH electrolyte. Based on the results above, Co3 O4 sheets were further utilized in a 2 M KOH aqueous electrolyte and exhibit a maximum specific capacitance of 288 F g −1 at a current density of 1 A g −1 .